PENGARUH LATIHAN INCREMENTAL VERTICAL HOP TERHADAP DAYA LEDAK OTOT TUNGKAI PADA KLUB BOLA VOLI PUTRA LIPAT KAIN SELATAN - Ammar, Rizki; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: From the observations of researchers in the field at the South Lipat Kain men's volleyball club, there are several weaknesses that appear along with the occurrence of players in training and in volleyball matches, namely there are still many leg muscle deficiencies when jumping. This can be seen when doing a smash or block. So that the South Lipat Kain men's volleyball club often loses during matches. The purpose of this study was to determine the effect of incremental vertical hop exercise on leg muscle explosive power in the South Lipat Kain men's volleyball club. The population in this study amounted to 20 people using total sampling, so the sample amounted to 20 people. The instrument in this research is the vertical jump test. The data obtained were analyzed using t-test. Based on the t-test, it produces a T-count of 9,24 with a T-table of 1.792, so it is accepted, at an alpha level of 0.05. It can be concluded that there is an effect of vertical hop incremental exercise on the explosive power of the leg muscles in the South Lipat Kain men's volleyball clubKey Words: Incremental Vertical Hop, Limb Muscle Explosive Power